The Cost-Effectiveness of the Kiva Antibullying Program: Results from a Decision-Analytic Model - Mattias Persson; Linn Wennberg; Linda Beckman; Christina Salmivalli; Mikael Svensson (Springer New York LLC, 2022)
Bullying causes substantial suffering for children and adolescents. A number of bullying prevention programs have been advocated as effective methods for counteracting school bullying. However, there is a lack of economic evaluations of bullying prevention programs assessing the “value for money.” The aim of this study was to assess the cost-effectiveness of the Finnish bullying prevention program KiVa in comparison to “status quo” (treatment as usual) in a Swedish elementary school setting (grades 1 to 9). The cost-effectiveness analysis was carried out using a payer perspective based on a Markov cohort model. The costs of the program were measured in Swedish kronor and Euros, and the benefits were measured using two different metrics: (1) the number of victim-free years and (2) the number of quality adjusted life years (QALYs). Data on costs, probability transitions, and health-related quality of life measures were retrieved from published literature. Deterministic and probabilistic sensitivity analyses were carried out to establish the uncertainty of the cost-effectiveness results. The base-case analysis indicated that KiVa leads to an increased cost of €829 for a gain of 0.47 victim-free years per student. In terms of the cost per gained QALY, the results indicated a base-case estimate of €13,823, which may be seen as cost-effective given that it is lower than the typically accepted threshold value in Swedish health policy of around €50,000. Further research is needed to confirm the conclusions of this study, especially regarding the treatment effects of KiVa in different school contexts.